Liquidity of commercial banks in Portugal and Spain - Marco Amaral (European Journal of Government and Economics (EJGE), 2021)
Liquidity is very important for the functioning of financial markets, especially for the banking sector, because one of the critical aspects in the banking business is precisely the process of transforming short-term funds and placing them in the medium and long term. This paper aims to comprehensively assess the liquidity positions of Portuguese and Spanish commercial banks through different liquidity ratios for the period from 2002 to 2015 and understand whether the liquidity management strategy differs by bank size. To this end, unconsolidated balance sheet data were used, which were obtained from the banks annual reports. The sample includes a significant part of the Portuguese and Spanish banking sector (not only by the number of banks, but also by the representation in banks total assets). The results obtained show that Spain's banks' liquidity indicator has decreased over the last four years. In contrast, bank liquidity indicator in Portugal varied slightly positively during the period 2002-2006 but decreased sharply between 2010 to 2015. Bank liquidity increased slightly during the period of the financial crisis in both countries, namely between from 2007 to 2009. Finally, it is concluded that smaller banks have less fluctuating liquidity management, i.e., large and medium-sized banks show greater variation in bank liquidity in the period under analysis, i.e., they are less liquid.
Keywords: G21; 330; banking liquidity; financial entities; crisis